2016
DOI: 10.5713/ajas.15.0940
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genetic Diversity Using 15 Simple Sequence Repeats Markers in Long Term Selected Japanese Quail Lines

Abstract: Japanese quail is still used as a model for poultry research because of their usefulness as laying, meat, and laboratory animals. Microsatellite markers are the most widely used molecular markers, due to their relative ease of scoring and high levels of polymorphism. The objective of the research was to determine genetic diversity and population genetic structures of selected Japanese quail lines (high body weight 1 [HBW1], HBW2, low body weight [LBW], and layer [L]) throughout 15th generations and an unselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is the opinion of Machado et al (2003), who states that if the value of H0 is lower than that of He, it indicates the degree of endogamy (marriage in groups). Karabag et al (2016) stated that high genetic diversity has an observed heterozygosity value of more than 0,5. Heterozygosity is a parameter used to measure the level of genetic diversity in a population based on allele frequencies at each locus (Wang et al, 2015).…”
Section: Heterozygositymentioning
confidence: 99%
“…It is the opinion of Machado et al (2003), who states that if the value of H0 is lower than that of He, it indicates the degree of endogamy (marriage in groups). Karabag et al (2016) stated that high genetic diversity has an observed heterozygosity value of more than 0,5. Heterozygosity is a parameter used to measure the level of genetic diversity in a population based on allele frequencies at each locus (Wang et al, 2015).…”
Section: Heterozygositymentioning
confidence: 99%
“…These findings indicate that the population is diverse. High genetic diversity has heterozygosity values of more than 0.50 (Karabağ et al 2016). The results of genotype frequency, allele frequency, heterozygosity, and chi-square analysis (χ 2 ) of the prolactin gene at various locus are presented in Table 2.…”
Section: Genotype Frequency Allele Frequency and Prolactin Gene Heterozigositymentioning
confidence: 99%
“…The observed heterozygosity value was 0.306 and equally to the expected heterozygosity (Table 1), it indicates that the population is relatively diverse. According to Wang et al (2011), heterozygosity is an index to use for estimating the genetic diversity levels in the population, and the heterozygosity value more than 0.5 is considered high genetic diversity (Karabag et al, 2016). The PIC value as showed in the Table 1 was 0.260 that indicated the polymorphic at PRL/PstI locus had moderate level because of the PIC ranking in 0.25<PIC<0.5 according to Botstein et al (1980).…”
Section: Resultsmentioning
confidence: 99%